Power factor correction in switched mode power supply for computers using canonical switching cell converter. Issue 2 (1st February 2015) - Singh, Shikha; Bist, Vashist; Singh, Bhim; Bhuvaneswari, Gurumoorthy
Abstract : This study presents a novel power factor correction (PFC) technique using a canonical switching cell (CSC) converter applicable to multi‐output switched mode power supply (SMPS) used in personal computers (PCs). The CSC converter at the front end of this single‐phase fed SMPS operates in discontinuous conduction mode that offers inherent PFC for wide range of varying input voltages. It is cascaded to an isolated half‐bridge multi output dc–dc converter for obtaining multiple dc voltages that are stiffly regulated and isolated from each other as per the requirement of the PC. The proposed SMPS is designed, modelled and its performance is investigated under steady state and dynamic operating conditions for varying input voltages and loads. It is found that the proposed design is able to offer excellent power factor and low total harmonics distortion at the utility interface as shown in investigations carried on simulation and experimental studies. A comparison of conventional SMPS with proposed PFC‐based SMPS vividly brings out the merits of the latter. Further, a comparison is made with other types of front end converters to investigate the relative merits and demerits of the CSC converter over other front end converters.